Comparative study of analytical/semi-analytical methods for prediction of axial strength of cold-formed steel wall panels with sheathing. Issue 2 (3rd April 2022) - Sonkar, Chanchal; Mittal, Achal Kumar
ABSTRACT: Load-bearing cold-formed steel (CFS) wall panels comprise of a stud (C-section), track (U-section) and sheathing. Sheathing is fastened to the CFS frame with self-drilling screws, which has an effect on the axial load-carrying capacity of panels. Experiments are complex and often expensive as they require use of different resources (raw material, manpower etc.). Therefore, conducting experiments is not always possible and an efficient design tool is necessary. Few studies are present in literature on comparing the effectiveness of available design methodologies. For the first time, an attempt is made to compare all the three (03) presented mathematical models together to predict the axial strength of CFS wall panels with sheathing. The present study examines the effectiveness of such analytical/semi-analytical tools, namely, Rayleigh-Ritz (R-R) method, Differential equation of equilibrium (DEEq) method and Constrained and Unconstrained Finite Strip Method – Direct Strength Method (CUFSM-DSM) for estimation of axial load-carrying capacity of sheathed CFS panels. The results show that CUFSM-DSM can be utilized meritoriously for evaluation of sheathed CFS wall panels.